The role of perceptions in pedestrian quality of service (2019)
"The aims of this thesis were: firstly, to test the forecasting performance of some methodologies identified to calculate the PPSI considering the categories of different inputs (flow-capacity relation, objective data, and perceptual information). Secondly, to analyze their applicability to Bogotá?s local context. Thirdly, to analyze the individual and joint effect of the different groups of predictors (environmental, sociodemographic, physical, and perceptual) on the perceived QoS. Fourthly, to develop a cognitive map that describes how pedestrians perceive their QoS considering the positive and negative effects over them when walking. Fifthly, to propose a model to forecast sidewalk QoS (SQoS) using objective (e.g., physical) and subjective (e.g., perceptions) attributes. To fulfill the objectives of this research, 1056 pedestrian responses were gathered, considering their perceptions when walking, including their perception of the SQoS. In addition, data related to objective on-site attributes, was collected for 30 different sidewalks in the city of Bogotá. Then, to calculate the methodologies' performance in Bogotá, the PPSI values were calculated using 28 different methodologies and compared with the pedestrian perception of the SQoS. Performance was evaluated through a match score calculation, by the difference between the predicted value and the pedestrian's QoS perception, and by a ?^2 test. To analyze pure and joint effects of the different groups of predictors on the perceived QoS, 15 different models were developed that considered the groups individually, in pairs, and as groups of three and four. Then, the models were compared using the partial coefficient of determination (R2), the adjusted R2, and the F-test. In addition, a SEM approach was used to propose a cognitive map explaining the perceived QoS. Finally, a QoS forecast model was estimated from different approaches (i.e., OLS, ordered probit, and MIMIC)."--Tomado del Formato de Documento de Grado.